World Economic Outlook, April 2012 : Growth Resuming, Dangers Remain. (World Economic Outlook; World Economic Outlook ;, 2012)
The April 2012 issue of the World Economic Outlook assesses the prospects for the global economy, which has gradually strengthened after a major setback during 2011. The threat of a sharp global slowdown eased with improved activity in the United States and better policies in the euro area. Weak recovery will likely resume in the major advanced economies, and activity will remain relatively solid in most emerging and developing economies. However, recent improvements are very fragile. Policymakers must calibrate policies to support growth in the near term and must implement fundamental changes to achieve healthy growth in the medium term. Chapter 3 examines how policies directed at real estate markets can accelerate the improvement of household balance sheets and thus support otherwise anemic consumption. Chapter 4 examines how swings in commodity prices affect commodity-exporting economies, many of which have experienced a decade of good growth. With commodity prices unlikely to continue growing at the recent elevated pace, however, these economies may have to adapt their fiscal and other policies to lower potential output growth in the future.